Utility of far-field effects from tip-assisted Raman spectroscopy for the detection of a monolayer of diblock copolymer reverse micelles for nanolithography. Issue 18 (4th May 2021) - Arbi, Ramis; Hui, Lok Shu; Dittrich, Maria; Turak, Ayse
Abstract : A modified inverted Raman system using the far field effects of a tip can selectively enhance the signal from a uniform monolayer of diblock copolymer micelles. Mechanisms of enhancement can be determined from comparison with other Raman techniques. Abstract : A modified set-up for Raman spectroscopy is proposed to utilize an AFM probe in a regime beyond the dependence on near field optics. Possible mechanisms for the observed enhancement have been explored through comparisons to spectra from other enhanced Raman techniques, including surface enhanced Raman, interference enhanced Raman and polarized Raman spectroscopies. The effects of polarization, focusing and interference are heightened when near field effects are diminished, giving rise to spectral enhancement. This technique allows for the characterization of a sub-20 nm monolayer of polystyrene- block -poly(2 vinyl pyridine) reverse micelles and paves the way for a promising method of non-destructive analysis of large self-assembled arrays of colloids.